Beyond the "Like": How People Respond to Negative Posts on Facebook. Issue 2 (3rd April 2019) - Spottswood, Erin; Wohn, Donghee Yvette
Abstract : New features of social network platforms afford users the ability to navigate potentially sensitive situations in ways they could not before. This study surveyed 260 Facebook users to uncover how people are using this social media platform's new "reaction" buttons to respond to others' posts about negative topics such as traumatic life situations, catastrophic current or past events, and interpersonal crises. Results suggest that users do not perceive the reaction buttons as adequate tools to help them interact with those that are close to them. Instead, these new paralinguistic digital affordances seem to help users engage in social grooming.